The Mean Time of Strip Domain Stay in Metastable State - K, J.Kadhum; I.R.Agool; Sh.K.Al-Jorany (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
The phenomenon of the thermoinduced jumps of the step domains length in imperfect magnetic films with perpendicular with anisotropy is studied. For describing of the strip domain transitions into other metastable states, the stochastic equation of its head movement is used. In this equation the spatial non-uniformities of the medium are modeled by the restricted random function, and thermal fluctuations by the Gaussian white noise. The dependences on the temperature and the bias field of the mean time of strip domain stay in a metastable state were calculated by the methods of the Markovian processes theory